2021
DOI: 10.1101/2021.04.19.440391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prostaglandin E2directly inhibits the conversion of inducible regulatory T cells through EP2 and EP4 receptors via antagonizing TGF-β signalling

Abstract: Background and Purpose: Regulatory T (Treg) cells are essential for control of inflammatory processes by suppressing Th1 and Th17 cells. The bioactive lipid mediator prostaglandin E2 (PGE2) promotes inflammatory Th1 and Th17 cells and exacerbates T cell-mediated autoimmune diseases. However, the actions of PGE2 on the development and function of Treg cells, particularly under inflammatory conditions, are debated. In this study, we examined whether PGE2 had a direct action on T cells to modulate de novo differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Indeed, the expression and role of PGE 2 receptors EP2/4 and, thus, the regulation of cell behavior and immunological effects of PGE 2 (e.g., Treg induction) are complex and context‐dependent (disease, tissue, co‐signal). For instance, while PGE 2 has the potential to support Treg expansion by TGF‐ß‐Smad2/3 signaling (English et al , 2009; Cho et al , 2015), it has also been shown to inhibit this signal via stimulation of ERK1/2, PI3K/AKT, and 3’5’‐cAMP phosphorylation, which degrade Smad2/3 signaling (Thomas et al , 2007; Goepp et al , 2021). Whereas our settings suggest that induction of PGE 2 may contribute to a mechanism by which parasitic worms induce Tregs to control host immune attack, it may inhibit unwanted suppressive Treg activity in distinct immunological settings and tissue environments (e.g., tumor environment, intestine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the expression and role of PGE 2 receptors EP2/4 and, thus, the regulation of cell behavior and immunological effects of PGE 2 (e.g., Treg induction) are complex and context‐dependent (disease, tissue, co‐signal). For instance, while PGE 2 has the potential to support Treg expansion by TGF‐ß‐Smad2/3 signaling (English et al , 2009; Cho et al , 2015), it has also been shown to inhibit this signal via stimulation of ERK1/2, PI3K/AKT, and 3’5’‐cAMP phosphorylation, which degrade Smad2/3 signaling (Thomas et al , 2007; Goepp et al , 2021). Whereas our settings suggest that induction of PGE 2 may contribute to a mechanism by which parasitic worms induce Tregs to control host immune attack, it may inhibit unwanted suppressive Treg activity in distinct immunological settings and tissue environments (e.g., tumor environment, intestine).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the suppressive effect of PGE 2 on immune cells is affected by TCR‐signaling. Thus, PGE 2 inhibited Treg conversion via EP2 and EP4 in co‐stimulation of murine splenic, colonic, and peripheral blood human naïve T cells with TGF‐ß in presence of TCR activators (αCD3/αCD28) and/or cytokines (IL‐2, IL‐12) (Narumiya et al , 1999; Fulton et al , 2006; Neil et al , 2008; Goepp et al , 2021). In our hand, with no TCR activators or co‐stimulation, PGE 2 rather supports TGF‐ß signaling (or vice‐versa) as the simultaneous inhibition of both TGF‐ß and PGE 2 signals synergistically prevented Treg induction.…”
Section: Discussionmentioning
confidence: 99%